2016
DOI: 10.1111/vox.12437
|View full text |Cite
|
Sign up to set email alerts
|

Persistent aggregates in apheresis platelet concentrates are commonly collected from donors with a history of aggregate donation

Abstract: Platelet apheresis sometimes causes persistent aggregates (PA). This study (n = 211) shows that changing the apheresis settings to reach fixed product volumes instead of yields does not influence PA incidence, even though PA products on average contain more platelets than controls. Furthermore, logistic regression was used to model if PA can be predicted on the basis of certain predonation parameters. PA donation history was the only parameter retained, proving a strong determinant of predictability [AUC = 0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Donor-related factors that may contribute to the appearance of aggregates cannot be overseen. Previously published studies found that only some donors were more often associated with the appearance of aggregates in APCs than others [1,6,8]. Our study confirmed this observation and suggested the possible additional donor-related factors for PA (donor age, BMI, number of previous donations).…”
Section: Feys Et Al Investigated Several Factors Insupporting
confidence: 90%
See 2 more Smart Citations
“…Donor-related factors that may contribute to the appearance of aggregates cannot be overseen. Previously published studies found that only some donors were more often associated with the appearance of aggregates in APCs than others [1,6,8]. Our study confirmed this observation and suggested the possible additional donor-related factors for PA (donor age, BMI, number of previous donations).…”
Section: Feys Et Al Investigated Several Factors Insupporting
confidence: 90%
“…There is a lack of studies on the effect of APCs with aggregates on the platelet corrected count increment in patients because APCs with persistent aggregates (PA) are in most cases routinely discarded in blood banks [1]. Some researchers found a strong relationship of PA in APCs with donor history of aggregates [6][7][8]. This could imply that there are one or more donor-related factors responsible for the occurrence of aggregates in APCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation